The social and moral elevation of our working classes - Haughton, James (Dublin Statistical Society, 1857)
I have indicated some means whereby the social and moral elevation of our working classes may be secured to an extent hitherto unknown among us; and I conclude by the expression of my full belief that all our efforts will prove unavailing unless they are sustained by high principle. The rich must show an example to the poor of manly virtue, of adherence to truth, of an abhorrence of all insincerity, of a strict regard to honour in all the relations of public and private life; of the exercise of that charity which thinketh no evil, if it be possible to think otherwise. Thus feeling and thus acting, they will be instrumental in assisting largely in the social and moral elevation of our working classes.
Read 16th March, 1857
Keywords: Working class; 314.15